2000
DOI: 10.1080/010503900424589
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of a Danish adaptation of the Tinnitus Handicap Inventory

Abstract: The objective of this study was to determine the reliability and validity of a Danish translation of the Tinnitus Handicap Inventory (THI), a self-report measure of perceived tinnitus handicap. The Danish version of the THI was administered to 50 patients reporting tinnitus as their primary complaint or secondary to hearing loss. Construct validity was assessed using tinnitus symptom rating scales, the Beck Depression Inventory (BDI), the State-Trait Anxiety Inventory (STAI), the Tinnitus Coping Style Question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
84
4
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(105 citation statements)
references
References 18 publications
14
84
4
3
Order By: Relevance
“…Some references corroborate the maintenance of an internal consistency of this tool even after translations and adaptations to other populations and languages 11,14,18 . TSQ is made up of twenty five questions, broken down in three groups.…”
Section: Introductionmentioning
confidence: 63%
“…Some references corroborate the maintenance of an internal consistency of this tool even after translations and adaptations to other populations and languages 11,14,18 . TSQ is made up of twenty five questions, broken down in three groups.…”
Section: Introductionmentioning
confidence: 63%
“…Assessment of tinnitus severity with at least one additional questionnaire is highly recommended. A majority of the participants favoured the THI as an additional questionnaire because the THI is thought to be validated in the largest number of languages (Zachariae et al, 2000;Herraiz et al, 2001;Paula Erika et al, 2005;Kleinjung et al, 2007) and may thus facilitate comparability between studies.…”
Section: Questionnaires As Instruments For Measuring Tinnitus and Relmentioning
confidence: 99%
“…Other studies (except that of Wilson et al 55 ) evaluating neuroticism in tinnitus sufferers also found a significant positive correlation between neuroticism and perceived tinnitus severity. 9,13,14 Similarly, some 9,13 but not all studies, 14 found significant inverse correlations between reduced extraversion and perceived tinnitus severity. To our knowledge, this is the first study to examine the role of emotional stability in tinnitus, whereas previous studies have predominantly described the personality trait of "emotional stability" as being part of a personality profile, for example, such as "psychotic characteristics of the MMPI."…”
Section: Discussionmentioning
confidence: 92%
“…This is a weakness of the study. Furthermore, since there is no consensus as to which personality traits may play a role in tinnitus, a heterogeneous set of measures was used in previous studies, including the normal or short version of the MMPI, 5,7,15,17,56 -58 the EPQ, 9,13,14,55 and the DSM-III-R or DSM-IV classification for psychiatric disorders. 7,10,59 -62 This heterogeneity makes comparisons between studies difficult and hinders us from conducting metaanalyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation